Training manual on spatial analysis of plant diversity and distribution - Scheldeman, Xavier; Zonneveld, M. van (2010)
This training manual is intended for scientists and students who work with biodiversity data and are interested in developing skills to effectively carry out spatial analysis based on (free) GIS applications with a focus on diversity and ecological analyses.